Promising physiological traits associated with nitrogen use efficiency in rice under reduced N application - Srikanth, Bathula; Subrahmanyam, Desiraju; Sanjeeva Rao, Durbha; Narender Reddy, Sadu; Supriya, Kallakuri; Raghuveer Rao, Puskur; Surekha, Kuchi; Sundaram, Raman Meenakshi; Neeraja, Chirravuri Naga (Frontiers in Plant Science, 2023)
Higher grain yield in high yielding rice varieties is mostly driven by nitrogen (N) fertilizer applied in abundant amounts leading to increased production cost and environmental pollution. This has fuelled the studies on nitrogen use efficiency (NUE) to decrease the N fertilizer application in rice to the possible extent. NUE is a complex physiological trait controlled multiple genes and yet to be completed deciphered in rice. With an objective of identifying the promising physiological traits associated with NUE in rice, the performance of 14 rice genotypes was assessed at N0, N50, N100 and N150 for four (two wet and two dry) seasons using agro-morphological, grain yield, flag leaf traits, photosynthetic pigments content, flag leaf gas exchange traits and chlorophyll fluorescence traits. Further, the data were used to derive various NUE indices to identify the most appropriate indices useful to screen rice genotypes at N50. Results indicate that with the increase in N application, cumulative grain yield increased significantly up to N100 (5.02 t ha-1), however, the increment in grain yield was marginal at N150 (5.09 t ha-1). The mean reduction of grain yield was only 26.66% at N50 ranging from 15.0 to 34.2%. The significant finding of the study is the identification of flag leaf chlorophyll fluorescence traits (Fv/Fm, ΦPSII, ETR and qP) and Ci associated with grain yield under N50, which can be used to screen N use efficient genotypes in rice under reduced N application. Out of nine NUE indices assessed, NUpE, NUtE and NUEyield were able to delineate the high yielding genotypes at N50 and useful to screen rice under reduced N conditions. Birupa emerged as one of the high yielders under N50, even though it is a moderate yielder at N100 and infers the possibility of cultivating some of the released rice varieties under reduced N inputs. The study indicates the possibility of existence of promising genetic variability for grain yield under reduced N, potential of flag leaf chlorophyll fluorescence and gas exchange traits as physiological markers and best suitable NUE indices to be deployed in rice breeding programs.